Influence of experimental variables on the measure of contact angle in metals using the sessile drop method - Schuster, Jonathan Maximiliano (2015)
The sessile drop method is an easy and fast method used to measure the contact angle between solids and liquids. The value of the contact angle is used in surface characterization, in particular the wettability of solid surfaces by the liquid and to calculate the surface free energy. In this work, we study the effects of the volume of the drop placed on the surface, the elapsed time between drop placing and measurement and the cleaning of the substrate (not cleaning, washed with ethanol or washed with acetone) in the value of the contact angle on Ti6Al4V and AISI 316 stainless steel. We found that drop asymmetry is a very important parameter that must be considered in CA measurements. Anasymmetry parameter used to qualify the drop asymmetry is proposed. It was also found that the degree of cleanliness produces dispersion in the contact angle values; on the other hand no differences were found between cleaning with ethanol or acetone. CA decreases with time and increases slightly with decreasing droplet volume.